IISR Pragati: new turmeric variety - Prasath, D; Eapen, Santhosh J; Sasikumar, B; Akshitha, H J; Leela, N K (Indian Horticulture, 2019)
The IISR Pragati is a new addition to the varietal wealth of spices in our country. Developed by the scientists of our Calicut (Kerala) based research institute, this variety provides 38 tonnes/ha of turmeric. It is a short-duration variety and becomes ready for harvesting in 180-200 days.